Antagonistic potentiality of six wheat rhizosphere fungi against leaf blight pathogen Bipolaris sorokiniana (Sacc.) Shoemaker (Bioresearch Communications, 2022)
Six wheat rhizosphere fungi (Aspergillus flavus, A. fumigatus, A. niger, Penicillium sp., Trichoderma harzianum and T. viride) were evaluated for their antagonistic potentiality towards sixteen isolates of Bipolaris sorokiniana (Sacc.) Shoemaker under different cultural groups. Colony interaction using duel culture technique, inhibition owing to volatile and non-volatile substances in different concentrations were performed. Among them Trichoderma harzianum showed the best performance (colony interaction 61.69-79.02%, volatile substances 44.14-61.34% and non-volatile culture filtrate 47.28-68.14% at 20% concentration) to control Bipolaris sorokiniana followed by Trichoderma viride, Aspergillus niger, Aspergillus flavus, A. fumigatus and Penicillium sp..Bioresearch Commu. 8(2): 1124-1131, 2022 (July)